Pilkada Provinsi Papua: Menjaga Stabilitas Melalui Politik Hukum dan Keamanan - Karolina R.S. Wenggi; Dedy Pribadi Uang; Timoty Yusuf Salama (Fakultas Politik Pemerintahan, 2025)
The Papua provincial election reflects the complex dynamics of local politics, influenced by legal-political and security factors. This study aims to analyze efforts to safeguard the stability of the Papua election through legal-political approaches and security strategies. Using a qualitative method, the research examines the challenges of implementing national unificatory regulations within Papua’s unique social, cultural, and geographical context. The findings reveal that the misalignment of regulations with local realities generates various issues, such as logistical disparities, weak supervisory systems, clashes between cultural practices and formal democratic principles, low political participation of women, and potential threats to both physical and digital security. Therefore, a reformulation of legal politics that is contextual and inclusive is required, including the drafting of special regulations that accommodate Papua’s socio-cultural particularities, such as the noken system; establishing Minimum Cost Standards (SBM) and adaptive administrative deadlines; strengthening the supervisory authority of Bawaslu to create balance between electoral institutions (Bawaslu and KPU); increasing the number of supervisory personnel; and providing training tailored to the local context. Furthermore, an integrated, adaptive, and participatory security strategy is necessary to realize fair, peaceful, and democratic elections in Papua. This includes enhancing cross-institutional coordination (KPU, Bawaslu, Police, and local government), expediting the distribution of logistics and honoraria for election officials, and strengthening information technology capacity as well as public digital literacy to counter hoaxes. Such strategies must also involve local actors and community leaders in maintaining stability and building public trust in state institutions to ensure peaceful, secure, and democratic elections in Papua.